2011
DOI: 10.7150/ijms.8.161
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of the PR Domain of Tumor Suppressor RIZ1

Abstract: Human tumor suppressor gene RIZ encodes two protein products, tumor suppressor RIZ1 and proto-oncoprotein RIZ2, which regulate cellular functions in a Yin-Yang fashion. The only structural difference between them is that RIZ2 lacks the N-terminal PR domain. In this study, we showed that RIZ1 mRNA expression level was elevated in stage IV of eight different types of cancer (stage III for prostate cancer), indicating that RIZ1 might play an important role in tumor metastasis, and the PR domain alone possessed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…RIZ-PR has tumor suppressor activity whereas RIZ-CR has been described to acts as an oncogene. 34,35 The probe used in our gene expression profiling analyses did not distinguish between the two transcripts. However, in the RT-qPCR validation of the expression levels, we analyzed the gene expression of each transcript and found that both the tumor-suppressive RIZ-PR and the oncogenic RIZ-CR were up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…RIZ-PR has tumor suppressor activity whereas RIZ-CR has been described to acts as an oncogene. 34,35 The probe used in our gene expression profiling analyses did not distinguish between the two transcripts. However, in the RT-qPCR validation of the expression levels, we analyzed the gene expression of each transcript and found that both the tumor-suppressive RIZ-PR and the oncogenic RIZ-CR were up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in RIZ1 mRNA expression has been reported at late stage of several cancers (Pastural et al, 2007;Sun et al, 2011). This may be due to the non-specific reaction of RIZ1 RT-PCR primers targeting PR domain which also bind to isoform d and MTB-ZF.…”
Section: Discussionmentioning
confidence: 97%
“…The PR domain of PRDM2/RIZ1 itself showed growth inhibitory and anticancer activities; indeed, it increased cell death when transfected in human hepatoma HuH7 cells [81]. Likewise, it inhibited cell proliferation and induced apoptosis in cultured primary meningioma cells and limited xenograft high-grade meningiomas tumor growth in nude mice through its methyltransferase activity [82].…”
Section: Prdm2mentioning
confidence: 99%